2002
DOI: 10.1111/1467-9280.00406
|View full text |Cite
|
Sign up to set email alerts
|

Attending to the Big Picture: Mood and Global Versus Local Processing of Visual Information

Abstract: Two experiments employed image-based tasks to test the hypothesis that happier moods promote a greater focus on the forest and sadder moods a greater focus on the trees. The hypothesis was based on the idea that in task situations, affective cues may be experienced as task-relevant information, which then influences global versus local attention. Using a serial-reproduction paradigm, Experiment 1 showed that individuals in sad moods were less likely than those in happier moods to use an accessible global conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
785
10
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 911 publications
(886 citation statements)
references
References 25 publications
65
785
10
11
Order By: Relevance
“…Next, participants were given the 24-trial perceptual, globalspecific focus task, modeled after Kimchi and Palmer (1982) and Gasper and Clore (2002). On each trial of this task, participants had to indicate which of two geometric comparisons was more similar to a target figure.…”
Section: Methodsmentioning
confidence: 99%
“…Next, participants were given the 24-trial perceptual, globalspecific focus task, modeled after Kimchi and Palmer (1982) and Gasper and Clore (2002). On each trial of this task, participants had to indicate which of two geometric comparisons was more similar to a target figure.…”
Section: Methodsmentioning
confidence: 99%
“…Why were the results of Baumann and Kuhl (2005) in the reverse direction to those not only of Gasper and Clore (2002) but also other studies in the area (e.g., Basso et al, 1996;Derryberry & Reed, 1998;Fredrickson, 2004;Gasper, 2004)? Baumann and Kuhl argued that the crucial distinction is that previous work examined only processing preferences, whereas they investigated the ability to switch between two types of processing.…”
Section: Encouragingmentioning
confidence: 87%
“…Though the relation between trait emotions and global versus local processing had previously been studied (Derryberry & Reed, 1998;Basso, Schefft, Ris, & Dember, 1996), Gasper and Clore (2002) were the first to examine directly the role of mood in global versus local processing. In their experiment, the relevant mood states were induced by asking participants to write about either a "happy and positive" personal life event, a "sad and negative" personal life event or -in the neutral condition -an "average, normal, typical weekday".…”
Section: Affect and Global Versus Local Processingmentioning
confidence: 99%
“…Research on cognitive processing styles, on the other hand, consistently showed that people in a negative emotional state show more focus on detailed information, whereas people in positive emotional states focus more on global information and generally accessible knowledge [e.g. [13-15]]. These findings would predict that negative emotional states increase the ability to exert inhibitory control.…”
Section: Introductionmentioning
confidence: 99%
“…In the unpleasant odour run, we expected the Stroop effect to be reduced compared to its non-olfactory control condition, as previous findings demonstrated increased inhibitory control under negative emotional states [12], and decreased control under positive emotional states [2]. Accounts of mood-dependent cognitive processing [13-15] would also suggest increased attention to details of the stimulus in a negative emotional state, and therefore reduced interference from the task-irrelevant stimulus dimension (word meaning). In contrast, the neutral odour should have no influence on the emotional state or on performance in the Stroop task.…”
Section: Introductionmentioning
confidence: 99%